Transplantation of Photoreceptor Precursors Isolated via a Cell Surface Biomarker Panel From Embryonic Stem Cell‐Derived Self‐Forming Retina. (27th May 2015) - Lakowski, Jorn; Gonzalez‐Cordero, Anai; West, Emma L.; Han, Ya‐Ting; Welby, Emily; Naeem, Arifa; Blackford, Samuel J. I.; Bainbridge, James W. B.; Pearson, Rachael A.; Ali, Robin R.; Sowden, Jane C.
Abstract Loss of photoreceptors due to retinal degeneration is a major cause of untreatable blindness. Cell replacement therapy, using pluripotent stem cell‐derived photoreceptor cells, may be a feasible future treatment. Achieving safe and effective cell replacement is critically dependent on the stringent selection and purification of optimal cells for transplantation. Previously, we demonstrated effective transplantation of post‐mitotic photoreceptor precursor cells labelled by fluorescent reporter genes. As genetically labelled cells are not desirable for therapy, here we developed a surface biomarker cell selection strategy for application to complex pluripotent stem cell differentiation cultures. We show that a five cell surface biomarker panel CD73(+)CD24(+)CD133(+)CD47(+)CD15(−) facilitates the isolation of photoreceptor precursors from three‐dimensional self‐forming retina differentiated from mouse embryonic stem cells. Importantly, stem cell‐derived cells isolated using the biomarker panel successfully integrate and mature into new rod photoreceptors in the adult mouse retinae after subretinal transplantation. Conversely, unsorted or negatively selected cells do not give rise to newly integrated rods after transplantation. The biomarker panel also removes detrimental proliferating cells prior to transplantation. Notably, we demonstrate how expression of the biomarker panel is conserved in the human retina and propose that a similar selection strategy will facilitate isolation of human transplantation‐competent cells for therapeutic application. Stem Cells2015;33:2469—2482